Archaeological historiography from architecture. About ideas, sites and architects (1919 - 2019) - Guzmán Juárez, Miguel (2018)
It is intended to give a review of the bibliographic production of those leading architects who focused their attention on archaeological architecture, researching the ancient societies of the Central Andes. There is a valuable information that could not be articulated to an integral discourse. Each architect is a «voice» that has built his contribution from a particular significant focus. They emphasize the pioneering works of Emilio Harth-terré (1921), through the generation of 1980: Carlos Williams, Carlos Milla and Santiago Agurto, like their main representatives, until the increasingly acute proposals of Jose Canziani or Alfio Pinasco among others. It is postulated to «rethink» the history of Andean architecture, looking at its processes based on interdisciplinary reflection. Architecture as a symbolic system from the Andean landscape.